Implementasi Projek Penguatan Profil Pelajar Pancasila Bertema Demokrasi pada Tahun Politik di SMPN 1 Mojosari - Eka Putri Dyahningtyas; Diki Rahmawan; Dwi Arif Rosanti; Dewi Indah Khapsari; Galuh Isbiyantari Putri; Riska Tri Wijaya; Silviana Bilqis Setiawan Putri; Ardhita, Wenny Indah; Nurhayati Ganinda (Pusat Riset dan Inovasi Nasional, 2024)
The background to conducting this research is to understand the importance of the project to strengthen the profile of Pancasila students in the context of democracy, which is an issue that cannot be ignored. The aim of conducting this research is to implement P5 activities at the junior high school level with the theme of democracy to introduce students to what democratic mechanisms are like and their implementation in the form of elections, especially in the upcoming elections, although in practice they only practice it when we carry out a general election. . The method used is a qualitative descriptive qualitative method. In this research, the techniques used in collecting data were interviews and documentation. The results obtained from the results of this research are research on the implementation of the project to strengthen the profile of Pancasila students with the theme of the voice of democracy in the political year at SMPN 1 Mojosari by going through the stages that have been carried out in the project activities to strengthen the profile of Pancasila students, which can provide students with an understanding of freedom. expression or the act of expressing opinions with equality lies in the view that all humans are considered equal in the eyes of the law.